2015
DOI: 10.1055/s-0035-1559595
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Speech Perception Tests in Relation to the Coding Strategy in Cochlear Implant

Abstract: Introduction  The objective of the evaluation of auditory perception of cochlear implant users is to determine how the acoustic signal is processed, leading to the recognition and understanding of sound.Objective  To investigate the differences in the process of auditory speech perception in individuals with postlingual hearing loss wearing a cochlear implant, using two different speech coding strategies, and to analyze speech perception and handicap perception in relation to the strategy used.Methods  This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…Hearing loss can also lead to impairment of the individual's communication, and can cause secondary issues involving other aspects, such as cognitive, emotional and social [1] [2].…”
Section: Introductionmentioning
confidence: 99%
“…Hearing loss can also lead to impairment of the individual's communication, and can cause secondary issues involving other aspects, such as cognitive, emotional and social [1] [2].…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted by Bazon et al two different speech coding strategies of different brands were compared and they found no significant difference in speech perception. 36 Yet in another study Jang et al worked on two different cochlear implant brands to investigate the postoperative performance and they found that there was no difference on open-set monosyllabic word, open-set disyllabic word and open-set sentence scores. 37 So, in this study we did not discriminate between the implant brands and we believe that postoperative performance of each brand is similar.…”
Section: Discussionmentioning
confidence: 99%
“…Оценка различий в более короткие сроки, на наш взгляд, затруднено ввиду необходимости привыкания к изменению звучания слогов и слов, а также необходимости накопления опыта использования. Сравнения, ранее проводимые другими авторами, были ограничены значительно более коротким временным промежутком (от двух недель до нескольких месяцев) [11,12], вследствие чего было затруднительно обнаружить значимые различия и определить предпочтения пациентов [13,12].…”
Section: Discussionunclassified